How did Amazon achieve CSR and some Sustainable Development Goals (SDGs) - climate change, circular economy, water resources and employee rights during COVID-19? - Wenxuan Yu; Abeer Hassan; Mahalaxmi Adhikariparajuli (Journal of Risk and Financial Management, 2022)
Stakeholders' demand for corporate social responsibility (CSR) not only creates pressure on the corporation, but corporations are also themselves aware about leading CSR activities' reporting and embedding sustainable activities to create value for the short, medium, and long-term. This research investigates the sustainable development and corporate social responsibility of Amazon as one of the most influential multinational enterprises in the world. In this regard, this study sheds light on how Amazon has combined its own interests with corporate social responsibility and sustainable development, and how they have responded to a series of challenges brought by economic globalization to corporate social responsibility and sustainable development. The results of this detailed investigation of Amazon from 2018 to 2020 show that Amazon has performed very well in terms of social responsibility and sustainable development. In particular, climate, environment, carbon emissions and other natural measures. However, there are some shortages in terms of human rights, such as insufficient protection and care for employees during the COVID-19 pandemic, and labor union issues. In addition, the study concluded that Amazon has sufficient experience to balance profit and corporate social responsibility. In response to the challenges of globalization, Amazon has also adjusted its sustainable development strategy in a timely manner, which can be used as a reference for other multinational enterprises.
Keywords: 650; COVID-19; Sustainability; Amazon; CSD; CSR